The Politics of Sequence: Data Sharing and the Open Source Software Movement. - Stevens, Hallam (Information & Culture, 2015)
The Bermuda Principles (1996) have been celebrated as a landmark for data sharing and open science. However, the form that data sharing took in genomics was a result of specific technological practices. Biologists developed and adopted technologies of the nascent World Wide Web and Free and Open Source Software (FOSS) communities for sharing biological information. These technologies supported decentralized, collaborative, and nonproprietary modes of production in biology. Such technologies were appealing not merely because they were expedient for genomic work but because they also offered a way of promoting a particular form of genomic practice. As the genome sequencing centers scaled up their sharing efforts, a small group of computer-sawy biologists used these tools to promote the interests of the public genome sequencing effort. The agreements at Bermuda should be understood as part of this attempt to foster a particular form of genomic work.